Analysis of ESTs generated from inner bark tissue of an Acacia auriculiformis x Acacia mangium hybrid - Yong, Christina Seok Yien; Choong, Chee Yen; Cheong, P.L.; Pang, Sze Lei; Nor Amalina, R.; Harikrishna, Jennifer Ann; Mat-Isa, Mohd Noor; Hedley, P.; Milne, Linda; Vaillancourt, R.; Wickneswari, R. (Springer Verlag, 2011)
The majority of plant expressed sequence tags (ESTs) available in the public databases are from non-woody species such as Arabidopsis, maize, soybean, and rice, with the exception of the model tree species, Populus. In this study, we report the first EST database constructed from the commercially important tree species Acacia. ESTs were generated from pooled RNA extracted from the mature, intermediate, and young inner bark tissues of an Acacia auriculiformis x Acacia mangium hybrid. Finally, 3,182 high-quality ESTs were analyzed representing a total of 1,982 unique transcripts (663 contigs and 1,319 singletons) for the inner bark cDNA library. A total of 1,053 unigenes (1,750 ESTs) showed similarities with protein sequences in public database where 867 were significant matches (E value ≤ e-10). Further analysis performed on unigenes with significant matches and known functions identified 231 genes including genes involved in cellulose, lignin, and hemicellulose biosynthesis. For cDNA library validation, quantitative real-time RT-PCR was performed to study the expression levels of the cellulose and lignin genes identified from this EST database in the phloem tissue of A. mangium, A. auriculiformis, and A. auriculiformis x A. mangium hybrid. All the seven candidate genes were expressed in all the individuals studied confirming the dependability of the EST database. The cDNA library and the EST database constructed are valuable resources for forest tree research aiming towards understanding the genetic control of wood formation and in the future endeavors to modify wood and fiber profile through marker-assisted breeding programs. © 2010 Springer-Verlag.